2017
DOI: 10.1017/cem.2017.197
|View full text |Cite
|
Sign up to set email alerts
|

MP31: The contrarian effect: how does a Choosing Wisely focused knowledge translation initiative affect emergency physician practice in a high awareness-low investigation environment?

Abstract: following: taking notes, eating, only reading). Both groups showed significant improvements in their test scores (Asthma: 22% improvement, Toxicology: 29%; p < 0.01 for both), with blog posts demonstrating a larger but non-significant difference (RM-ANOVA, Topic*Modality F(1,59) = 0.001, p = 0.973). Conclusion: This study suggests that podcasts and blog posts significantly improve medical student knowledge retention to a similar degree, but differ in usage conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…A total of 603 unique studies were identified though the electronic and gray literature searches. Figure outlines the study selection process, which resulted in a total of five included studies . Twenty‐one studies were excluded for the following reasons: not a primary research study ( n = 13), ineligible study population (e.g., non‐ED population; n = 4), absence of a control group ( n = 2), or absence of an intervention aimed at reducing imaging ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 603 unique studies were identified though the electronic and gray literature searches. Figure outlines the study selection process, which resulted in a total of five included studies . Twenty‐one studies were excluded for the following reasons: not a primary research study ( n = 13), ineligible study population (e.g., non‐ED population; n = 4), absence of a control group ( n = 2), or absence of an intervention aimed at reducing imaging ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…All five studies, published between 1987 and 2017, implemented the intervention in the EDs of teaching hospitals in Canada, the United States, or the United Kingdom and employed before–after study designs. Three studies were published in peer‐reviewed journals and two studies were conference abstracts . All studies recruited adult patients presenting to the ED with LBP; however, no study specified how many patients presented with traumatic or nontraumatic LBP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations